The reproducibility of handheld ERGs recorded with skin electrode and natural pupils - Sommer, Chiara; Turgut, Ferhat; Saad, Amr; Becker, Matthias D.; Al-Sheikh, Mayss; Davis, C. Quentin; Rahn, Ulrike; Barboni, Mirella T. S.; DeBuc, Delia Cabrera; Somfai, Gábor Márk (Documenta ophthalmologica, 2025)
Purpose: To investigate the reproducibility of hand-held full-field electroretinogram (ERG) to determine the minimum change required in longitudinal measurements to reach statistical significance. Methods: The study included 27 healthy volunteers, aged 45–65. Light-adapted (ISCEV standard) full-field ERGs measured with the RETeval device (LKC Technologies, Germantown, MD, USA) were recorded using non-invasive skin electrodes, followed by a second examination 1–14 days later. Intersession variability of the a- and b-waves, the flicker responses (light intensity 85 Td·s, frequency 28.3 Hz) and the photopic negative response (PhNR, 38 Td·s on 380 Td blue) were assessed. Results: The mean standard deviations were 0.86, 0.83, 0.40 and 3.24 ms for a-wave, b-wave, flicker and PhNR peak times, respectively. Coefficient of variations (CV) were 32%, 22%, 18%, and 19.2% for the amplitudes of the a-wave, b-wave, flicker and PhNR, respectively. Conclusion: While flicker ERGs had the smallest variability, ISCEV standard a-wave and b-wave times also had variability less than 1 ms, indicating excellent reproducibility. Amplitudes were more variable, with the a-wave amplitude having the most variability. While it depends on disease, longitudinal studies utilizing ERG timing are expected to be more likely to show statistically significant results due to low inter-session variability.
Online veröffentlicht: 25. November 2025
Gesehen am 28.01.2026